Brussels in Strasbourg: Theoretical Reflections on the Impact of European Union Law on the Case-Law of the European Court of Human Rights - Kūris, Egidijus (Teisė, 2024)
The article presents a theoretical reflection on one of the aspects of the impact of European Union law on the case-law of the European Court of Human Rights from the perspective of the competition between these two legal systems, and in the broader context of the perception of international law as a fragmentised legal reality. It is argued that the interplay between the law of the Convention and EU law is horizontal, as none of these legal systems is and perhaps will never be subordinated to the other. It is shown that one of the tools of harmonisation of the two legal systems is the so-called mutually friendly interpretation, and it is demonstrated how EU law-friendly (and, more broadly, international law-friendly) interpretation has been undertaken by the ECtHR in the cases of Al-Dulimi ([GC] 2016), Hanan ([GC] 2021) or Bosphorus ([GC] 2005). It is also discussed how the ECtHR’s approach to EU law as particular international law is reflected in the structure of the judgments of this Court.
Keywords: collision rule; conflict of legal systems; Constitutional Court of the Republic of Lithuania; Convention for the Protection of Human Rights and Fundamental Freedoms; Court of Justice of the European Union; European Court of Human Rights; European Union law; fragmentation of international law; friendly interpretation; internalisation of international and EU law; preliminary ruling